Kajian Yuridis terhadap Kerugian yang ditimbulkan Akibat Kecelakaan Perkeretaapian Berbasis Nilai Keadilan - Churniawan, Erifendi; Agustriana, Titiek Masdini; Priyanto, Sapto (Wajah Hukum, 2024)
Railway transportation is one of the mass transportation modes widely used by the Indonesian people. However, train accidents often occur and cause losses to the victims. Therefore, the value of justice becomes very important as a basis for examining the issue of losses due to train accidents. This research aims to analyze the regulation of liability and compensation related to railway accidents in Indonesian law and evaluate whether these regulations are based on the value of justice. This research is a normative legal research that analyzes the relevant laws and regulations using a statutory and conceptual approach. The type of data used is secondary data in the form of primary legal materials such as laws and government regulations, as well as secondary legal materials such as books and journals, using analytical-prescriptive descriptive qualitative analysis methods. The research results explain that the regulation of liability and compensation related to railway accidents in Indonesia is regulated in several laws and regulations such as the Railway Law, Government Regulations, and related ministerial regulations. In general, these regulations require railway facility operators to provide compensation to service users who suffer material and immaterial losses due to accidents caused by the operator's fault. The amount of compensation is determined based on the calculation of losses suffered by the victim, considering factors such as medical expenses, loss of property, and physical or psychological suffering. Although it attempts to accommodate the values of justice, there are still shortcomings in terms of unclear criteria, types, and amounts of compensation that must be given, as well as the potential for differing interpretations or inconsistent implementation, which could lead to injustice for accident victims.